Catboy - Walters, Eric, 1957- (Orca Book Publishers, 2011)
While trying to adjust to his move from a small northern town to the heart of Toronto, Taylor becomes interested in caring for a colony of feral cats in a junkyard, but when development threatens the colony, Taylor wonders how he can help them.